Who really contributes to information science research? An analysis of disciplinarity and nationality of contributors to ten top journals - D. Lund, Brady (Malaysian Journal of Library and Information Science, 2020)
Understanding the shifts in contributions to the discipline of Information Science, and its subdisciplines/specialties of Library Science and Information Science, is important for researchers, educators, and advocates in this field. This study analyzes the disciplinary and national affiliations of authors in ten top Information Science journals from 2015-2019. Findings indicate that significant discrepancies exist among the authorship of journals examined, with journals like Journal of Documentation having a large majority of authors from Library and Information Science schools, while journals like Information Processing and Management have only a small number of computers from Library and Information Science relative to disciplines such as computer science. Nationality findings indicate that Europe, North America, and Asia have significant representation in these Information Science publications, though developing countries are severely underrepresented compared to developed countries. These findings highlight significant discrepancies in contributions to Information Science research and the need for more Library and Information Science contributors, particularly from developing countries. International and interdisciplinary collaboration may be particularly helpful in achieving this goal.